The Role of Telehealth in Sideline Management of Sports-Related Injuries. Issue 1 (February 2021) - Subramanyam, Venkat; Day, Molly A.; Kinderknecht, James J.
The COVID-19 pandemic has affected the ability of the sports medicine physician to be present to participate in in-person sideline evaluation of the injured athlete. The purpose of this review is to assess existing literature regarding the utilization of telehealth for sideline evaluation and management of the injured athlete, as well as to identify further areas of research. With the rapid incorporation of telehealth visits, the utilization and capabilities of telemedicine continue to expand. A number of evidence-based resources are available to support medical providers to develop and utilize video evaluation for the sideline evaluation of sports-related injuries. Future research, including the development of validated, modified examination techniques and technologies, will allow for improved interactive physical examinations, which may be better utilized for sideline evaluation.